Customary law of procedure and evidence :a juridical and ethnographic study in the Limpopo Province, South Africa - Monyamane, Phillip Lesetja (My University, 2024)
Customary law has undeniably experienced a tumultuous journey within the South African legal landscape. Its historical trajectory includes a dark chapter marked by legislative injustice, exemplified by the enactment of the Black Administration Act 38 of 1927. However, there has also been a glimmer of hope on this path, symbolised by the insignificant acknowledgment and acceptance of customary law in the Law of Evidence Amendment Act 45 of 1988. Every endeavour was made to belittle customary law, pervert it and erode it of its true fabric as an amalgamation of customs, religion and the lived realities of the indigenous people. The conscious failure by the morally reprehensible colonialists and the segregationalist Apartheid state to appreciate the correct paradigm of customary law has resulted in an intentioned nonlaw that has been rather prolific in both literature and jurisprudence. It is the view of this study that it has long been overdue to cleanse customary law off the stains of bad faith draftsmanship and rid it off the perversion caused to it by its colonial past. To achieve this, the study is intentional about de-linking customary law from the other system in order to properly understand, define, establish, advance and promote traditional justice. In doing this, the study proceeded from the premise that customary law, as a system, is an inseparable matrix of customs, religion and the lived realities of the people living according to that system. This lived reality as innate in the system itself necessitated the type of methodology adopted for study and encouraged extra care in dealing with the pervasion achieved through official documents on this system. Ethnography was intentionally opted for as the correct methodology because its definition and scope is based on magnifying the reality of the subject studied. This view corresponds directly with the need to ground indigenous reality in traditional dispute resolution. As a methodology that embraces pluralism, it allows for adaptation to the methods as the study develops. This study invites researchers to undertake customary law inquiry within the correct location that enhances Natives’ cultural capital. At the end, this study aims to contribute meaningfully to transformative action by properly aligning the customary law paradigm to the realities of the people as envisioned in the definition of customary law. The theoretical and conceptual framework of study accepts that the knowledge paradigm in general and legal training in particular was not constructed for the benefit of Natives. As a result of the foreign ideology of knowledge, customary law was penetrated and perverted through the lenses of a law foreign to it. This meant that a foreign reality was endorsed in the shared South African worldview and education is the vehicle through which reality of Natives vii was perverted or oppressed. Notwithstanding this, it is contended in this study that the Constitution in the Republic of South Africa validates this colonial conquest by failing to expressly locate the cultural capital of Natives in its text. This need for promotion of indigenous reality through constitutional text is based on colonial and apartheid bad faith in the erosion of Native worldview. Foreign language(s), as a cultural artefact, in particular English, was given a privileged position in South Africa through legislation. This privileging, it is argued, was not nor does it fully embrace the epistemological edges of customary law. To properly locate these edges, the study invites us to engage in new pursuits of traditional epistemology. For current purporses, this pursuit entails the adoption of community cultural wealth as the lenses through which traditional justice must be considered. Within this lense, the study denotes that Natives have legal capital that has always and continue to enable them to resolve legal issues in their communities. Properly understood, however, it is argued in this study that traditional courts are a socially embedded fora that is both fluid, flexible and comprehensive.
Thesis (LLD.) -- University of Limpopo, 2024
Keywords: Customary Law; Customary marriage; Constitutionalism; Access to justice; Indigenous cosmology; Community; Community Cultural Wealth; Customary law; Customary law -- South Africa; Marriage (Customary law); Ethnology